Дослідження змін букального та назального епітелію у хворих на риніт вагітних - Яремчук, С. Е.; Степанюк, Я. В.; Лозовська, Ю. В.; Yaremchuk, S. E.; Stepanyuk, Ya. V.; Lozovs'ka, Yu. V. (Українське наукове медичне товариство лікарів-оториноларингологів, 2013)
Изучение морфологии клеток слизистой оболочки является высокоинформативным и неинвазивным методом исследования. Результаты цитологических исследований четко отображают общее состояние организма и выявляют преморбидный фон. Целью настоящей работы было изучение клеток назального и буккального эпителия у здоровых беременных и небеременных женщин, а так же у больных ринитом беременных. Выявлены патологические изменения в клетках как назального, так и буккального эпителия при рините беременных. Для клеток буккального эпителия характерна выражен-ная грубосетчатая структура хроматина, значительное количество клеток с гетерохроматинизирова-ными ядрами. Для назального эпителия в основном типична грубозернистая структура хроматина и значительное количество апоптозных клеток. Эти изменения свидетельствуют о выраженном нарушении функциональном состоянии генома вследствие воздействия экзо- и/или эндогенных факторов, приводящих к гибели клеток. The investigation of morphology of the mucous cells is a highly informative and non-invasive method of research. The results of cytological studies clearly show the overall health and identify premorbid back-ground. The aim of this study was to examine the cells of nasal and buccal epithelium in healthy pregnant and non-pregnant women, as well as in women suffering from pregnancy rhinitis. Abnormalities in the cells of both nasal and buccal epithelium in the cases of preg-nant rhinitis were revealed. For buccal epithelial cells a coarse-grained chromatin structure and a significant number of cells with heterochromatinic nucleuses are typical. Nasal epithelium is mainly characterized by a coarse-grained structure of chromatin and a significant apoptotic cells. These changes indicate expressed infringement of the functional status of the genome due to the impact exo- and/or endogenous factors leading to cell death.
Study of changes buccal and nasal epithelium in patients with rhinitis in pregnancy
Keywords: ринит; назальный эпителий; буккальный эпителий; беременность; rhinitis; nasal epithelium; buccal epithelium; pregnancy